Cardiac-induced liver deformation as a measure of liver stiffness using dynamic imaging without magnetization tagging—preclinical proof-of-concept, clinical translation, reproducibility and feasibility in patients with cirrhosis. - Chouhan, Manil D.; Fitzke, Heather E.; Bainbridge, Alan; Atkinson, David; Halligan, Steve; Davies, Nathan; Lythgoe, Mark F.; Mookerjee, Rajeshwar P.; Menys, Alex; Taylor, Stuart A. (Abdominal Radiology, 2021)
Purpose: MR elastography and magnetization-tagging use liver stiffness (LS) measurements to diagnose fibrosis but require physical drivers, specialist sequences and post-processing. Here we evaluate non-rigid registration of dynamic two-dimensional cine MRI images to measure cardiac-induced liver deformation (LD) as a measure of LS by (i) assessing preclinical proof-of-concept, (ii) clinical reproducibility and inter-reader variability, (iii) the effects of hepatic hemodynamic changes and (iv) feasibility in patients with cirrhosis. Methods: Sprague–Dawley rats (n = 21 bile duct ligated (BDL), n = 17 sham-operated controls) and fasted patients with liver cirrhosis (n = 11) and healthy volunteers (HVs, n = 10) underwent spoiled gradient-echo short-axis cardiac cine MRI studies at 9.4 T (rodents) and 3.0 T (humans). LD measurements were obtained from intrahepatic sub-cardiac regions-of-interest close to the diaphragmatic margin. One-week reproducibility and prandial stress induced hemodynamic changes were assessed in healthy volunteers. Results: Normalized LD was higher in BDL (1.304 ± 0.062) compared with sham-operated rats (1.058 ± 0.045, P = 0.0031). HV seven-day reproducibility Bland–Altman (BA) limits-of-agreement (LoAs) were ± 0.028 a.u. and inter-reader variability BA LoAs were ± 0.030 a.u. Post-prandial LD increases were non-significant (+ 0.0083 ± 0.0076 a.u., P = 0.3028) and uncorrelated with PV flow changes (r = 0.42, p = 0.2219). LD measurements successfully obtained from all patients were not significantly higher in cirrhotics (0.102 ± 0.0099 a.u.) compared with HVs (0.080 ± 0.0063 a.u., P = 0.0847). Conclusion: Cardiac-induced LD is a conceptually reasonable approach from preclinical studies, measurements demonstrate good reproducibility and inter-reader variability, are less likely to be affected by hepatic hemodynamic changes and are feasible in patients with cirrhosis.